Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Contextual Teaching and Learning di MI Ziyadatul Iman - Agustina Sholihah; Vioni Saputri (Lembag, 2025)
This research was motivated by initial observations at Ziyadatul Iman Elementary School, which showed that the school used Student Worksheets (LKS) without textbooks, and there was a need for relevant and engaging teaching materials. This study aimed to develop Student Worksheets (LKPD) based on Contextual Teaching and Learning (CTL) at Ziyadatul Iman Elementary School. The development model used was the ADDIE model, with the trial subjects being grade IVB students at Ziyadatul Iman Elementary School.. The validation results showed that the LKPD was very valid by linguists (95%), valid by material experts (80%), and media experts (80%). The responses of teachers (96%) and students (94% of small groups, 92.6% of large groups) were also very good. In conclusion, this LKPD is suitable for use to improve student understanding and learning outcomes.